I just got stuck and need help seeing what other steps I can take.
This answer expands on lemontree's comment in case that wasn't clear.
Instead of making an assumption on line 5 of $P \to Q$, derive $P \to Q$ using conjunction elimination ($\land$ Elim) referencing line 1 which is the premise $(P \to Q) \land R$.
Lines 6, 7, and 8 should stay the same.
On line 9 you can discharge the assumption $P$ that you made on line 4 using conditional introduction ($\to$ Intro) referencing lines 4-8. This will give you the desired result $P \to (Q \land R)$.
That should complete the proof.